Epidermolysis Bullosa (EB) Acquisita in an Adult Patient with Previously Unrecognized Mild Dystrophic EB and Biallelic COL7A1 Mutations - Liliana Guerra; Angelo Giuseppe Condorelli; Paola Fortugno; Valentina Calabresi; Cristina Pedicelli; Giovanni Di Zenzo; Daniele Castiglia (Medical Journals Sweden, 2018)
Circulating anti-type VII collagen autoantibodies are frequently detected in patients with recessive dystrophic epidermolysis bullosa (RDEB). However, evidence supporting their pathogenic role in inducing epidermolysis bullosa acquisita (EBA) has been provided for only one individual with dominant dystrophic epidermolysis bullosa (DDEB). We describe here a patient who presented with dystrophic toenails since early childhood and developed trauma-induced skin blisters and oral erosions at age 26 years. Direct immunofluorescence showed IgG deposits with a u-serrated pattern along the cutaneous basement membrane zone, while no change in the expression of collagen VII could be detected by antigen mapping. High-titre anti-collagen VII antibodies were detected by enzyme-linked immunoassay (ELISA). In parallel, sequencing of epidermolysis bullosa (EB) genes identified compound heterozygous COL7A1 missense c.410G>A (p.Arg137Gln) and splicing c.3674C>T (p.Ala1225_Gln1241del) mutations, previously unrecognized in dystrophic epidermolysis bullosa (DEB). Thus, our patient had RDEB "nails-only" and developed mechanobullous EBA in adulthood. These data support a pathogenic role of circulating autoantibodies to collagen VII in inducing EBA in selected patients with DEB. Unforeseen worsening of skin symptoms in DEB should prompt laboratory investigations for EBA.